Dichomeris Hübner, 1818 (Lepidoptera, Gelechiidae, Dichomeridinae) from Cambodia, including associated Chinese species - Zhao, Shengnan; Park, Kyu-Tek; Bae, Yang-Seop; Li, Houhun (Zootaxa, 2017)
In a faunal study of the micromoths in Cambodia, thirteen species of the genus Dichomeris (Gelechiidae, Dichomeridinae) are recognized, including associated Chinese species. Eight species are described as new: D. arcuata sp. nov., D. splendiptera sp. nov., D. samkosensis sp. nov., D. foliforma sp. nov., D. magnimacularis sp. nov., D. hainanensis sp. nov., D. cambodiensis sp. nov., D. acutivalvata sp. nov. Five species are newly recorded for Cambodia: D. orientis Park & Hodges, D. fuscusitis Li & Zheng, D. obsepta (Meyrick), D. microsphena Meyrick, and D. matsumurai Ponomarenko & Ueda. . Images of adults and genitalia are provided.